The need for strategic development of safety sciences - Busquet, Francois; Hartung, Thomas (My University, 2017)
The practice of risk assessment and regulation of substances has largely developed as a patchwork of circumstantial additions to a nowadays more or less shared international toolbox. The dominant drivers from the US and Europe have pursued remarkably different approaches in the use of these tools for regulation, i.e., a more risk-based approach in the US and a more precautionary approach in Europe. We argue that there is need for scientific developments not only for the tools but also for their application, i.e., a need for Regulatory Science or, perhaps better, Safety Science. While some of this is emerging on the US side as strategic reports, e.g., from the National Academies, the NIH and the regulatory agencies, especially the EPA and the FDA, such strategic developments beyond technological developments are largely lacking in Europe or have started only recently at EFSA, ECHA or within the flagship project EU-ToxRisk. This article provides a rationale for the creation of a European Safety Sciences Institute (ESSI) based on regulatory and scientific needs, political context and current EU missions. Moreover, the possible modus operandi of ESSI will be described along with possible working formats as well as anticipated main tasks and duties. This mirrors the triple alliance on the American side (US EPA, NIH and FDA) in revamping regulatory sciences. Moreover, this could fit the political agenda of the European Commission for better implementation of existing EU legislation rather than creating new laws.
Keywords: regulatory toxicology, testing strategies, scientific policy advice, alternative test methods; 570